2009
DOI: 10.2146/ajhp080083
|View full text |Cite
|
Sign up to set email alerts
|

Survey of physicians regarding clinical pharmacy services in academic emergency departments

Abstract: Objectives Previous reports have shown that clinical pharmacists improve quality of care, but the extent of pharmacist involvement in emergency departments (EDs) is unknown. The objective of this study was to determine the prevalence and nature of clinical pharmacy services in academic EDs. Methods All programs listed in a national Emergency Medicine physician residency catalog in June 2006 were surveyed using a web-based survey instrument, which was developed based on literature and expert consensus. Only t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…In a survey disseminated to 99 academic EDs, 30% reported coverage by a dedicated ED pharmacist, 22% reported partial coverage, and 6% reported the presence of a pharmacy satellite. 24 According to the American Society of Health-System Pharmacists (ASHP) guidelines on emergency medicine pharmacist services, a pharmacist's intervention is most valuable when it is performed prior to medication administration. 20 This concept was further supported when Patanwala et al 21 conducted a study to determine whether pharmacist activities led to the interception of medication errors.…”
Section: Discussionmentioning
confidence: 99%
“…In a survey disseminated to 99 academic EDs, 30% reported coverage by a dedicated ED pharmacist, 22% reported partial coverage, and 6% reported the presence of a pharmacy satellite. 24 According to the American Society of Health-System Pharmacists (ASHP) guidelines on emergency medicine pharmacist services, a pharmacist's intervention is most valuable when it is performed prior to medication administration. 20 This concept was further supported when Patanwala et al 21 conducted a study to determine whether pharmacist activities led to the interception of medication errors.…”
Section: Discussionmentioning
confidence: 99%
“…New US survey results of facilities offering emergency medicine residency programs found that 8% of institutions had a dedicated pharmacist in the emergency department 24 h/day, 22% had partial coverage, and 77% had no pharmacist coverage. 12 Two previous US studies found dedicated pharmacists in 3.5% 13 and 14% 14 of hospital emergency departments. In those hospitals where pharmacists are available in the emergency department, orders for pediatric patients, particularly orders for identified high-alert medications, can be given priority for review by the pharmacist before administration.…”
Section: Discussionmentioning
confidence: 95%
“…According to a recent survey of academic health care facilities with EM residencies, only 30% had some type of EM pharmacist coverage with 8% having 24/7 coverage. 11 Furthermore, many institutions did not utilize their ED pharmacist resources to their full potential (the definition of which included: provision of drug therapy recommendations or patient counseling and advice regarding cost effectiveness of drug therapy). This survey demonstrates growth of ED pharmacy services over published reports earlier in the decade.…”
Section: Background and Historymentioning
confidence: 99%